TikTok as pedagogical tool for english language learning: a systematic literature review - Jantan Anua Jah, Nurain; Tahreb, Nurus Syahidah; Ibrahim, Qistina; Hamzah, Intan Fitri Aisyah; Abd Halim, Nurhazwani (GADING Journal for the Social Sciences, 2024)
TikTok, a social media platform featuring short videos, has been utilised as an educational tool to help students develop communication skills, particularly in English language learning. This systematic literature review examines the effectiveness of TikTok as a pedagogical tool for enhancing English language acquisition. Using the Preferred Reporting Items for Systematic Review and Meta- Analyses (PRISMA) 2020 framework, the study provides a comprehensive analysis of scholarly articles from SCOPUS and Web of Science (WoS). The review identified key themes related to TikTok's impact on students' learning experiences by grouping studies based on the main issues they explored, such as the learning outcomes highlighted and the ways TikTok was used as a teaching tool or instructional strategy in English classrooms. By exploring both the advantages and challenges of using TikTok, this study contributes to the expanding body of research on digital learning tools and their role in modern education, advocating for innovative strategies in English language teaching and learning.